Field research 2008 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2009)
Includes research reports from these locations: Harvey County Experiment Field, South Central Kansas Experiment Field, Irrigation and North Central Kansas Experiment Fields, Kansas River Valley Experiment Field, East Central Kansas Experiment Field, and Harvey County Experiment Field.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 2008; Kansas Agricultural Experiment Station contribution; no. 09-208-S; Kansas; Agriculture; Crops; Weed control; Disease control; Fertilizer; Irrigation